Learning While Learning: Psychology Case Studies for Teaching Regression - Ciaran Evans; Alex Reinhart; Erin Cooley; William Cipolli (Journal of Statistics and Data Science Education)
In this article, we explore the use of two published datasets for teaching a wide range of students about regression models, with a particular focus on interaction terms. The two datasets come from recent psychology studies on beliefs about poverty and welfare, and about the dynamics of groups projects. Both datasets (and their original research papers) are accessible to students, and because of their context, students can learn about data collection, measurement, and the use of statistics when studying complex social topics, while using the data to learn about regression analysis. We have used these data for a range of in-class activities, journal paper discussions, exams, and extended projects, at the undergraduate, master’s, and doctoral levels. Supplementary materials for this article are available online.